2021
DOI: 10.7554/elife.68217
|View full text |Cite
|
Sign up to set email alerts
|

The hepcidin regulator erythroferrone is a new member of the erythropoiesis-iron-bone circuitry

Abstract: Background: Erythroblast erythroferrone (ERFE) secretion inhibits hepcidin expression by sequestering several bone morphogenetic protein (BMP) family members to increase iron availability for erythropoiesis. Methods: To address whether ERFE functions also in bone and whether the mechanism of ERFE action in bone involves BMPs, we utilize the Erfe-/- mouse model as well as β–thalassemic (Hbbth3/+) mice with systemic loss of ERFE expression. In additional, we employ comprehensive skeletal phenotyping analyses as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Iron metabolism also plays a significant role in bone remodeling through action of erythroferrone (ERFE), a protein secreted by erythroblasts in bone marrow, a negative regulator of hepcidin. ERFE was shown to bind to BMP family-2, -6, and -2/6 heterodimer ( Castro-Mollo et al, 2021 ; Wang et al, 2020 ). By using Erfe -/- mice and β-thalassemic mice with systemic loss of ERFE expression ( Hbb th 3/+ ; Erfe -/- ), our group showed that ERFE was highly expressed in osteoblasts even compared with erythroblasts, and the absence of ERFE caused high bone turnover and significant bone loss.…”
Section: Osteogenesis Hematopoiesis and Angiogenesis In Local Partner...mentioning
confidence: 99%
“…Iron metabolism also plays a significant role in bone remodeling through action of erythroferrone (ERFE), a protein secreted by erythroblasts in bone marrow, a negative regulator of hepcidin. ERFE was shown to bind to BMP family-2, -6, and -2/6 heterodimer ( Castro-Mollo et al, 2021 ; Wang et al, 2020 ). By using Erfe -/- mice and β-thalassemic mice with systemic loss of ERFE expression ( Hbb th 3/+ ; Erfe -/- ), our group showed that ERFE was highly expressed in osteoblasts even compared with erythroblasts, and the absence of ERFE caused high bone turnover and significant bone loss.…”
Section: Osteogenesis Hematopoiesis and Angiogenesis In Local Partner...mentioning
confidence: 99%
“…In recent years, there is growing evidence of the relationship between erythropoiesis, bone mineral metabolism and iron homeostasis. Recently, a mechanism responsible for the activation of osteoclasts in thalassemic patients has been described that could be associated to cytokine dysregulation and, in particular, to the modification of the RANK/RANKL/OPG axis, which is essential for the regulation of osteoclastogenesis ( 16 , 17 ). The OPG/RANK/RANKL system is essential for the regulation of osteoclastogenesis.…”
Section: Bone Disease In β-Thalassemiamentioning
confidence: 99%
“…Therefore, ERFE seems to be key in the recently described erythropoiesis-iron-bone circuit, by modifying the availability of BMP. Therefore, ERFE appears to be an important link between abnormal erythropoiesis, iron metabolism alteration, and loss of BMD in β-thalassemia ( 16 , 17 ).…”
Section: Bone Disease In β-Thalassemiamentioning
confidence: 99%
See 2 more Smart Citations